Fibreoptic bronchoscopic positioning of double-lumen tubes. Issue 12 (December 2017) - Foley, Karen A.; Slinger, Peter
Abstract: Double-lumen tubes (DLTs) should be placed using a fibreoptic bronchoscope. This allows correct positioning of the bronchial lumen in the chosen mainstem bronchus. It also ensures that the blue bronchial cuff does not obstruct the side to be ventilated when it is inflated under direct vision. Fibreoptic bronchoscopy facilitates correct positioning of the ventilatory side slot of a right DLT over the right upper lobe bronchus. The anaesthetist must know the fibreoptic tracheo-bronchial anatomy to properly position left- and right-sided DLTs and should always reconfirm the position of a DLT with fibreoptic bronchoscopy after repositioning the patient. Maintaining orientation (anterior-posterior) during fibreoptic bronchoscopy is crucial to positioning a DLT, particularly after the patient has been turned to the lateral position. A fibreoptic bronchoscope can also be used as a guide to direct a DLT under direct vision into its correct position.